1995
DOI: 10.1136/bmj.311.7019.1543
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fundholding in general practice on prescribing habits three years after introduction of the scheme

Abstract: Objectives-To observe changes in prescribing practice that occurred after the introduction of fundholding in first wave practices and to contrast these with changes occurring in similar nonfundholding practices.Design-Prospective observational study. Setting-Oxford region fundholding study. Subjects-Eight first wave fundholding practices and five practices that were not interested in fundholding in 1990-1, which were similar in terms of practice size, training status, locality, and urban rural mix. Three of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 4 publications
2
27
0
Order By: Relevance
“…Of the remaining, one paper was excluded as only the abstract was in English [6]; six papers were excluded as the studies were not designed to specifically evaluate the practices of DD [7][8][9][10][11][12] (for example effects of fundholding on practices across catchments). Nine papers were excluded due to the absence of an adequate comparison group [13][14][15][16][17][18][19][20][21] (for example comparing dispensing general practitioners vs. non-dispensing medical specialists); and two papers did not describe their methodology [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining, one paper was excluded as only the abstract was in English [6]; six papers were excluded as the studies were not designed to specifically evaluate the practices of DD [7][8][9][10][11][12] (for example effects of fundholding on practices across catchments). Nine papers were excluded due to the absence of an adequate comparison group [13][14][15][16][17][18][19][20][21] (for example comparing dispensing general practitioners vs. non-dispensing medical specialists); and two papers did not describe their methodology [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with research into changes made by general medical practitioners, [24][25][26] this study assessed change within general dental practice based upon self reports. Such an approach has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…35 Regardless of the type of study, the majority have shown positive effects on savings. The benefits of the intervention studies, namely the use of fewer and cheaper prescriptions, are shown to disappear over time, 36,37 which suggests the need for repeating the intervention at frequent intervals. Rational prescribing messages should be promoted at national and local medical meetings and the input from local practitioners should be considered.…”
Section: 15mentioning
confidence: 99%